Poverty Reduction Support Credits : An Evaluation of World Bank Support - World Bank (Washington, DC, 2012)
Poverty Reduction Support Credits (PRSCs) were intended to help countries implement comprehensive, country-owned development strategies to promote growth, improve social conditions, and reduce poverty. PRSCs were intended to ease conditionality, make annual flows to recipient countries predictable and integrated with their budgets, strengthen domestic budget processes, provide a framework for donor harmonization, and focus on achieving results. In terms of process, PRSCs have worked well. Findings show that they incorporated many envisaged changes in design and implementation. These include stronger country ownership, eased conditionality, and a shift of focus towards public sector management and pro-poor service delivery. PRSCs balanced tensions between predictability and program credibility. Although PRSCs differed from preceding adjustment loans, development policy lending today has converged towards a similar design. PRSCs today are subject to the same guidelines as other Development Policy Loans (DPLs). Differences remain in practice in terms of the association with PRSPs, broad scope, programmatic nature, and country performance. The evaluation recommends either that PRSCs be phased out as a separate brand name or that these differences be clearly spelled out.